2010 2nd International Conference on Reliability, Safety and Hazard - Risk-Based Technologies and Physics-of-Failure Methods (I 2010
DOI: 10.1109/icresh.2010.5779542
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Binary Decision Diagram using Genetic algorithm

Abstract: Fault tree analysis is a widely accepted technique to assess the probability and frequency of system failure in many industries.Traditionally statistical methods and boolean reductions is employed to analyze the fault tree. Even though the fault tree approach is commonly used for system reliability analysis, there are inherent limitations in terms of accuracy and computational efficiency. For the evaluation of minimal cut-set using fault tree method, it is required to solve large number of boolean expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Combining branch and bound with ordered best search which leads to exact minimization is also proposed [16]. Genetic algorithm-based approaches have been proposed by many researchers [17]- [19]. A comparison of the genetic algorithm-based approach and branch and bound-based technique with other dynamic techniques such as scatter search is also proposed which concluded that the genetic algorithm-based approaches and branch and bound techniques are superior to other dynamic techniques [20].…”
Section: Introductionmentioning
confidence: 99%
“…Combining branch and bound with ordered best search which leads to exact minimization is also proposed [16]. Genetic algorithm-based approaches have been proposed by many researchers [17]- [19]. A comparison of the genetic algorithm-based approach and branch and bound-based technique with other dynamic techniques such as scatter search is also proposed which concluded that the genetic algorithm-based approaches and branch and bound techniques are superior to other dynamic techniques [20].…”
Section: Introductionmentioning
confidence: 99%
“…But FT model and BDD structure exponentially increase along with the number of variables, and the size of BDD structure is very sensitive to variable ordering as described by Vesely, 1970and Awinash et al, 2010(Vesely, 1970Kumar et al, Dec 2010). Therefore, when solving a large FT in BDD algorithm, the high memory consumption is a limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Another application is the location of cutsets, minimal collections of links that if deleted will disconnect a graph. Work on this problem appears in [1], [23]. The problem of clustering a graph into sets of tightly coupled subgraphs or communities is the subject of [21], [25].…”
Section: Introductionmentioning
confidence: 99%